Análisis de la resistencia a largo plazo de elementos de concreto armado expuestos a condiciones ambientales adversas - Barrera Toscano, Rene Alfonso (2024)
The present study addresses the analysis of the long-term resistance of reinforced concrete elements exposed to adverse environmental conditions. The main objective is to identify the critical factors that affect the durability of these structures. The methodology uses a mixed approach that integrates quantitative and qualitative methods. Quantitative methods focus on measuring deterioration rates and evaluating the effectiveness of mitigation techniques through accurate data, while the qualitative component explores experiences and decisions of professionals in the design and maintenance of structures. The main results highlight that moisture compromises the structural resistance by facilitating the carbonation and corrosion of the reinforcing steel. The implementation of corrosion inhibitors and the use of additives such as microsilicate and polymer fibers show that they are effective in improving the durability of concrete. Preventive maintenance practices and the use of advanced technologies such as embedded sensors are essential to extend the useful life of reinforced concrete. The conclusion highlights that the adoption of a comprehensive approach that includes improvements in material and continuous maintenance is crucial to improve the long-term resistance of reinforced concrete in adverse conditions.